Stability in the general three-body problem - Mardling, R (2001)
In this contribution I review the theory of resonance and stability. I then discuss how one can predict, from first principles, the dynamical stability of arbitrary three-body configurations. Tidal stability of binaries and other tidally interacting systems can be predicted using an identical formulation which uses the chaos theory concept of resonance overlap.